Diffusion processes in advanced technological materials - Gupta, Divandar (William Andrew Pub., 2005)
This new game book for understanding atoms at play aims to document diffusion processes and various other properties operative in advanced technological materials. Diffusion in functional organic chemicals, polymers, granular materials, complex oxides, metallic glasses, and quasi-crystals among other advanced materials is a highly interactive and synergic phenomenon. A large variety of atomic arrangements are possible. Each arrangement affects the performance of these advanced, polycrystalline multiphase materials used in photonics, MEMS, electronics, and other applications of current and developing interest. This book is written by pioneers in industry and academia for engineers, chemists, and physicists in industry and academia at the forefront of today's challenges in nanotechnology, surface science, materials science, and semiconductors.